A Simple and Low‐Tech Heat‐Shock Method to Increase Genome Editing Efficiency in Plants. Issue 12 (5th December 2022) - Blomme, Jonas; Ribera, Júlia Arraiza; Develtere, Ward; Jacobs, Thomas B.
Abstract: CRISPR/Cas is now the standard technique to generate novel plant genotypes. However, optimizing the efficiency of the system continues to be an aspect of research and development. One of the improvements for increasing mutagenesis efficiency in different species is the application of heat stress. However, many experimental setups are limited by the requirement of using dedicated climate chambers to impose heat stress and by difficulties in the phenotyping of soil‐grown plants. Here, we describe a simplified heat stress assay for in vitro –grown plants that can be completed in 6 days using commonly available laboratory equipment. We show that three 24‐hr heat shocks (3×HS) at 37°C alternated with 24 hr of recovery at 21°C efficiently increases indel rates of LbCas12a and Cas9. We illustrate how visual mutant phenotypes ( pds3 and gl1 ) can assist in quantifying genome editing efficiency, and describe how to quantify genome editing efficiency using genotyping by Sanger sequencing. We also provide a support protocol to efficiently clone a CRISPR expression vector in a single step. Together, our methods allow researchers to increase CRISPR‐induced mutations using a low‐tech setup in plants. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : 3×HS protocol Basic Protocol 2 : Genotyping by Sanger sequencing Support Protocol : One‐step cloning of a CRISPR expression vector